Key Financial Indicators by the Size of the Construction Company - Czech Study - Vitkova, Eva; Kocourkova, Gabriela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Statistical data on the values of financial indicators in individual fields in the Czech Republic are provided by the Ministry of Industry and Trade. Updated values are issued quarterly. However, within the statistical samples, there are on average 34 companies focusing on construction. Moreover, no document specifies the size of the companies.
Keywords: construction industry; financial analysis; foreign capital; fixed assets; current assets; current liquidity; przemysł budowlany; analiza finansowa; kapitał zagraniczny; środki trwałe; aktywa obrotowe; płynność bieżąca; Republika Czeska